Transferrin receptor-mediated reactive oxygen species promotes ferroptosis of KGN cells via regulating NADPH oxidase 1/PTEN induced kinase 1/acyl-CoA synthetase long chain family member 4 signaling. Issue 1 (1st January 2021) - Zhang, Lingzhi; Wang, Fang; Li, Dongmei; Yan, Yufeng; Wang, Hongyan
ABSTRACT: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age. Abnormal ovarian folliculogenesis is the main factor responsible for PCOS. Iron metabolism plays a vital role in endocrine disorder. This study aimed to investigate the potentials of iron metabolism in PCOS and the underlying molecular mechanisms. Mice were injected with dehydroepiandrosterone (DHEA) to establish the PCOS model in-vivo. H & E staining was performed for histological analysis; qRT-PCR and western blot were employed to determine the mRNA and protein expressions. Immunofluorescence was used for mitochondrial staining. Cellular functions were detected using CCK-8 and PI staining assays. Ferric ammonium citrate (FAC) activates the transferrin receptor (TFRC), increases the iron content, and suppresses the cell viability of the human granulosa-like tumor cell line (KGN). However, TFRC knockdown suppressed ferroptosis of KGN cells. Iron uptake mediated the activation of NADPH oxidase 1 (NOX1) signaling, which induced the release of reactive oxygen species (ROS) and mitochondrial damage. Moreover, TFRC activated PTEN induced kinase 1 (PINK1) signaling and induced mitophagy; iron-uptake-induced upregulation of acyl-CoA synthetase long chain family member 4 (ACSL4) was required for mitophagy activation and glutathione peroxidase 4 (GPX4) degradation. Additionally, FAC increased iron uptake and suppressed the folliculogenesis in-vivo. In conclusion, TFRC increased the iron content, mediated the release of ROS, activated mitophagy, and induced lipid peroxidation, which further promoted the ferroptosis of KGN cells. Therefore, the inhibitory effects of TFRC/NOX1/PINK1/ACSL4 signaling on folliculogenesis can be a potential target for PCOS. uf0001